Relationships between barbell squat strength and weightlifting performance. Issue 4 (August 2019) - Lucero, Rhys AJ; Fry, Andrew C; LeRoux, Christopher D; Hermes, Matthew J
Weightlifters compete in the snatch, clean and jerk, and total (snatch + clean and jerk). Commonly used assistance exercises for training weightlifters are front barbell squats and back barbell squats. The purpose of this study was to determine relationships between the front barbell squats and back barbell squats one repetition maximum (1 RM) and the snatch, clean and jerk, and total 1 RM. Senior male competitive weightlifters ( n = 72) served as subjects in the survey. Significant correlations were found between front barbell squats and snatch, clean and jerk, or total 1 RM ( r 2 = 0.85, 0.88, and 0.87 respectively) and between back barbell squats and snatch, clean and jerk, or total 1 RM ( r 2 = 0.83, 0.84, and 0.83 respectively). Regression analyses indicate that 1 RM in the snatch, clean and jerk, and total are linearly related to the 1 RM in the front barbell squats and back barbell squats. Superior lifters appeared to be more efficient in using their back barbell squats strength during weightlifting compared to lower level lifters.